Relationship Between Self-Control and Academic Procrastination During The The Covid-19 Pandemic in Psychology Students Muhammadiyah University Bandung - Raka Atarek Haekal; Riyanda Utari; Nurlaela Hamidah (Psycho Holistic, 2022)
The COVID 19 pandemic has raised various problems in the economic, health, social sectors, especially education which have forced the teaching and learning process to be carried out online or distance learning. This triggers various problems in the academic world, one of which is academic procrastination behaviour encountered in students such as delaying doing and completing assignments. Although distance learning is carried out in their respective homes, in fact not all students are able to properly regulate and control their behaviour such as dividing time for things they like and doing academic activities. The purpose of this study was to determine the relationship between self-control and academic procrastination during the COVID-19 pandemic in Psychology students at the University of Muhammadiyah Bandung. This research is quantitative research with a correlational research design. The respondents in this study were 125 Psychology students at the University of Muhammadiyah Bandung, class 2017. 2018. 2019 and 2020. The sampling technique used was the probability sampling with proportionate stratified random sampling technique. The measuring instrument used in this study is self-control and procrastination scales. Analysis of research data using the Pearson's Product Moment correlation technique with the help of the SPSS 20.0 program for windows. Based on the calculation results obtained correlation value rxy = -0.711 with sig = 0.000 (p<0.05). This shows that there is a negative and significant relationship between self-control and academic procrastination in the strong correlation categorization. The r2 value is 0,506, meaning that the contribution of self-control to academic procrastination is 50,6%, there are 49,4% other factors besides self- control. The level of self-control possessed by Psychology students is low and the level of academic procrastination that is possessed is high.